Silk Fibroin-Alginate-Hydroxyapatite Composite Particles in Bone Tissue Engineering Applications In Vivo - Jo, You-Young (Int J Mol Sci, 2017)
The aim of this study was to evaluate the in vivo bone regeneration capability of alginate (AL), AL/hydroxyapatite (HA), and AL/HA/silk fibroin (SF) composites. Forty Sprague Dawley rats were used for the animal experiments. Central calvarial bone (diameter: 8.0 mm) defects were grafted with AL, AL/HA, or AL/HA/SF. New bone formation was evaluated by histomorphometric analysis. To demonstrate the immunocompatibility of each group, the level of tumor necrosis factor (TNF)-α expression was studied by immunohistochemistry (IHC) and quantitative reverse transcription polymerase chain reaction (qRT-PCR) at eight weeks post implantation. Additionally, osteogenic markers, such as fibroblast growth factor (FGF)-23, osteoprotegerin (OPG), and Runt-related transcription factor (Runx2) were evaluated by qPCR or IHC at eight weeks post implantation. The AL/HA/SF group showed significantly higher new bone formation than did the control group (p = 0.044) and the AL group (p = 0.035) at four weeks post implantation. Additionally, the AL/HA/SF group showed lower relative TNF-α mRNA levels and higher FGF-23 mRNA levels than the other groups did at eight weeks post implantation. IHC results demonstrated that the AL/HA/SF group had lower TNF-α expression and higher OPG and Runx2 expression at eight weeks post implantation. Additionally, no evidence of the inflammatory reaction or giant cell formation was observed around the residual graft material. We concluded that the AL/HA/SF composite could be effective as a scaffold for bone tissue engineering.